Phenolic and non-Phenolic Fractions of the Olive Oil Mill Wastewaters as Corrosion Inhibitor for Steel in HCl medium - Bouknana,D (2014)
The effect of the phenolic (OOMW-Ph) and non-phenolic (OOMW-NPh) fractions of the extract of olive oil mill wastewaters was evaluated as corrosion inhibitor of steel in molar hydrochloric using weight loss measurements and electrochemical polarisation. The results obtained reveal that the referred compounds reduce the corrosion rate. The inhibiting action increases with the concentration of the extract compounds to attain 88.9% and 89.1% of OOMW-Ph and OOMW-NPh, respectively. The increase in temperature leads to a decrease in the inhibition efficiency of the compounds in the temperature range 303 at 333 K. The adsorption isotherm of the inhibitors on the steel surface has been determined. The thermodynamic data of activation and adsorption are determined as well. The phenolic compound (bioactive) most abundant in OOMW extracts is hydroxytyrosol (4 -(2-hydroxyethyl) -1, 2-benzenediol), playing an important role in the effect of the anti-corrosion, either alone or in synergy with other two compounds (tyrosol and oleuropein (4 -(2-hydroxyethyl) phenol) which are present with considerable amounts.